Flipped Classroom Learning Model On Pjok Learning Outcomes Viewed From Learning Motivation - Dewi, Ni Luh Ayu Marlina; Wajeodi, H; Swadesi, I Ketut Iwan (UNIVERSITAS PAKUAN, 2023)
The application of learning models that are not in accordance with environmental conditions is one of the factors for students not being able to observe the material properly in the learning process in class, thus making low student learning outcomes. The purpose of this study is to determine the improvement of PJOK learning outcomes through a learning model. This research is a pseudo-experiment and archetype of 2x2 factorial design . The sampling technique used purposive sampling of 76 students. Data analysis with pre-test post-test control group design (gain score). Test the prerequisites of analysis through normality and homogeneous tests. The results of the descriptive analysis showed that students who followed the Flipped Classroom learning model had a pre-test score of 41.32 with a poor category and a post-test score of 77.11 with a very good category, while students who followed the STAD learning model had a pre-test score of 24.87 with a less good category and a post-test score 63.55 in the good category. It was concluded that the Flipped Classroom learning model is more effective than the STAD learning model.